Random Amplified Polymorphic DNA - Polymerase Chain Reaction (RAPD-PCR) Technique of Genetic Diversity of Silurus glanis - Al-Omairi, Majeed Sh. S. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Genetic diversity is essential for ensuring species resilience and supporting long-term ecological stability. Specific Background Silurus glanis, an ecologically and economically important freshwater fish in Iraq, is increasingly exposed to environmental pressures that may shape its genetic composition. Knowledge Gap Yet, information on the genetic variation between populations inhabiting the Euphrates and Tigris Rivers remains limited, particularly when assessed using RAPD-PCR molecular markers. Aims This study aims to evaluate the genetic diversity of S. glanis from both rivers using five RAPD primers to identify patterns of genetic similarity and differentiation. Results Analysis of 120 samples revealed 13 genetic loci, with 83.842% similarity and 16.154% genetic variation, indicating low diversity but high interpopulation resemblance. Novelty The study provides an updated genetic profile demonstrating the influence of local environmental conditions on the species’ genetic structure and suggesting potential gene flow between riverine populations. Implications These findings highlight the need for strengthened river ecosystem management and the application of molecular biomarkers to guide conservation strategies capable of preventing further genetic erosion and supporting the long-term sustainability of S. glanis populations.Highlight : The results show measurable genetic variation and high similarity between the two river populations. RAPD-PCR markers detected differences across loci that reflect environmental influences on genetic structure. The findings highlight the importance of monitoring river conditions to maintain the species’ genetic stability. Keywords : Genetic diversity, RAPD-PCR, Silurus glanis, Euphrates and Tigris populations, molecular markers